English-Russian Hybrid Words in Translated Text: On Linguistic Interference and Norms of Translation - Nefedova, Liliya; Krasnopeyeva, Ekaterina (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2020)
The article discusses the influence of Russian-English functional bilingualism of IT and tech specialists on the formation of translation norms in the corresponding field. The research is carried out within the framework of sociology of translation and descriptive approach in translation studies. It investigates the patterns in the usage of hybrid lexemes combining Russian and English graphemes, e.g. IoT-устройство (IoT-device), API-интерфейс (API-interface) and Open Source-приложение (open source application) in translations. Methodologically, the study resorts to the theoretical stance of sociology of translation, namely the concepts of translation norm, represented in the works by G. Toury and A. Chesterman, translator's habitus and the field of translation, as well as corpus-based methodology. It utilizes a comparable corpus of translated and non-translated articles published by Russian IT business magazines itWeek, Computerworld and Novosti Elektroniki (Electronics News) in 2017. Hybrids are shown to be more common in non-translated text, which can be viewed as an aspect of the expectancy norm. Qualitative study revealed the following patterns in hybrid usage in translation. Most of the hybrids used in translation are the direct result of the transfer of original English analytical structures. Hybrids are also used in translation as part of pragmatic positive interference, which shows the translator's reliance on the recipient's extensive background knowledge of the subject, as well as command of the English language. Interference, both positive and negative, is argued to be the aspect of the expectancy norm present in the field of technology-oriented media translation.